Inggris - Kholiq, Abdul (Veteran Law Review, 2023)
In practice of criminal justice system, a judge plays a fundamental role in making decision that will be imposed on the defendant. The Law on Judicial Power requires judges to widely disclose information and opinions from various groups and public participation. Amicus curiae concept is a mechanism that permits third parties who believe they are interested in a particular criminal case. However, the existence of amicus curiae in positive law has not been regulated explicitly or formally to explain how it is applied in criminal justice. While the judge plays a part in delivering a verdict on the defendant, it is anticipated to be founded on legal principles and a commitment of substantive public justice. This study employs a normative juridical research approach, utilizing secondary data acquired through library research and analyzed using qualitative methods and presented in a descriptive and explanatory format. The findings of this investigation that the position of amicus curiae can be known as stipulated in Article 5, paragraph (1) of the Judicial Power Act. In the application of the judge's decision to realize substantive justice, the judge does not only see a settlement in terms of formal law as a form of legal certainty, but the judge must also be able to see aspects of a sense of substantive justice by the expectations of the community as a seeker of justice.